A lump in throat: Qualitative study on hospitalization-related experiences among the parents of children with cancer - Rohollah Kalhor (Chronic Diseases Journal, 2019)
BACKGROUND: As the second leading cause of death, cancer is among the most stressful life events. It affects not only the afflicted patients, but also their families. Hospitalization of children with cancer faces their parents with many challenges and problems. This study was made to explore the hospitalization-related experiences among the parents of children with cancer.